2021
DOI: 10.1155/2021/5591719
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Conbercept Combined with Panretinal Photocoagulation vs. Panretinal Photocoagulation in the Treatment of Diabetic Retinopathy: A Meta-Analysis

Abstract: Objective. This meta-analysis aimed to compare the effect and safety of conbercept with panretinal photocoagulation (PRP) vs. PRP in the treatment of diabetic retinopathy (DR). Methods. Relevant studies were identified through systemic searches of PubMed, EMBASE, China National Knowledge Infrastructure, and Wanfang database up to December 2020. The results of conbercept and PRP in patients with DR were analyzed, including overall effectiveness, best corrected visual acuity, central macular thickness, and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…effectiveness and decreased the central thickness of the macula and other complications compared to the condition of the patients in the control group (14). Previous studies concentrated more on improving visual acuity and reducing macular edema in patients.…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…effectiveness and decreased the central thickness of the macula and other complications compared to the condition of the patients in the control group (14). Previous studies concentrated more on improving visual acuity and reducing macular edema in patients.…”
Section: Figurementioning
confidence: 89%
“…Intravitreal administration of Conbercept (IVC) is effective in treating PDR and DME cases. Treatment with IVC combined with PRP has a greater effect on functional outcomes than PRP monotherapy, including improvements in the visual acuity of the patients and reduction of macular edema (14). However, as studies on the therapeutic effects of IVC+PRP on high-risk PDR patients are limited, further research on this treatment method for high-risk PDR should be encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are numerous studies on the combination of PRP with intravitreal injections of anti-VEGF for treating PDR. However, the majority of research focuses on patients with severe non-proliferative DR, early-stage PDR, or diabetic macular edema (DME) [33][34][35][36] . HR-PDR patients, particularly those with VH who meet the criteria for PPV surgery, have been seldom explored in the literature [27,[37][38] .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis reported that compared with PRP monotherapy, the combination therapy of IVC and PRP (IVC+PRP) had a more substantial effect on functional outcomes, such as bettering patient vision and decreasing macular edema (14). Moreover, previous retrospective studies have suggested the possibility of using anti-VEGF drugs to reverse DR by inducing changes in retinal pathology and physiology through reperfusion (15).…”
Section: Introductionmentioning
confidence: 99%